The fading popularity of a local ecological calendar from Brunei Darussalam, Borneo - Nurzahidah Bakar; F. Merlin Franco (BMC, 2022)
Abstract Background Local ecological calendars are ecocultural frameworks that link temporal and spatial scales, contributing to resilience and adaptive management of natural resources and landscapes. They also facilitate management, access and withdrawal of provisioning ecosystem services. In this article, we describe how the ecological calendar of the Kedayan people of Brunei Darussalam links skyscape and biodiversity with sociocultural aspirations to foster adaptive management of landscape, and provide an understanding of the transmission of calendric knowledge in the community. Methods In 2018, we collaborated with sixteen purposively sampled knowledge keepers from the Kedayan community of Brunei Darussalam to document the Kedayan local ecological calendar, and develop a calendrical pictogram. Using a structured questionnaire, we then interviewed 107 randomly selected community members, to understand the contemporary relevance and popularity of the Kedayan calendar, and the transmission of calendric knowledge in the community. Results Our findings reveal that very few respondents (n = 27, 25.3%) are aware of the existence of Kedayan ecological calendar; majority (n = 80, 74.7%) were not aware of its existence. There is no statistically significant correlation between consulting healers, knowledge on appropriate time requisite to consult healers, and awareness and self-professed knowledge of Kedayan calendar. Only 14 (13.1%) of the respondents reported to have received some form of calendric knowledge, while the majority (86.9%; n = 93) never received any calendric knowledge. Only a negligible 1.9% reported to have transmitted calendric knowledge to others indicating a breakdown in transmission of calendric knowledge. Conclusion The calendric pictogram would help the community in revitalizing their calendar. However, the community will have to invest on enhancing transmission of calendric knowledge.